Behaviour of CI engine performance, combustion and exhaust emission with neem biodiesel at varied fuel injection rates. Issue 7 (3rd October 2019) - Karikalan, L.; Chandrasekaran, M.; Vinod Kumar, T.; Sridhar, R.
ABSTRACT: Motorisation and fast depletion of fossil fuel reserves and issues like global warming have led the researchers all over to look for substitute fuels. Biodiesel resulting from vegetable oil is being used around the globe to lessen air pollution and reduce the necessity of diesel fuel. The current study covers the various aspects of N20 neem biodiesel with increased fuel injection pressure. The blends of N20 were tested with increased fuel injection pressure to examine the characteristics such as brake thermal efficiency, fuel consumption, emission and combustion parameters. Experimental results indicated that N20 with 240 bar has a closer performance to diesel, reduced exhaust emission and improved combustion parameters.